Investigating the sterile surgical supply waste in laparotomy surgery - Mahmoud Bakhshi; Sanaz Mollazadeh; Mehdi Alkhan; Reza Salehinia; Mohammad Parvizi; Zahra Ebrahimi (BMC, 2024)
Abstract Background Operating rooms contribute to over 40% of hospital expenses, with a portion attributed to waste from single-use, sterile surgical supplies (SUSSS). This research aimed to determine the amount of cost wastage due to not using SUSSS during laparotomy procedures. Methods A descriptive-analytical investigation was conducted in two prominent teaching hospitals in Mashhad, Iran 2018. Seventy-seven laparotomy surgeries were scrutinized, documenting both used and unused disposable devices, with their respective costs being assessed. Data analysis was performed using SPSS version 16 software. Results The study revealed that during surgery in the operating rooms, waste of SUSSS averaged 5.9%. Betadine solution and sterile Gauze types were the top two contributors to resource wastage. Sterile Gauze types incurred the highest cost loss. The study found a significant correlation between cost wastage and surgeon experience (r = 0.296, P < 0.001) as well as surgery duration (r = 0.439, P < 0.001). Conclusion Inadequate management of available and commonly used disposable supplies leads to increased hospital expenses. Enhancing the surgical team's knowledge of sterile surgical supplies usage and making thoughtful selections can play a vital role in curbing health costs by minimizing waste of SUSSS in the operating rooms.